2020
DOI: 10.3846/jbem.2020.13225
|View full text |Cite
|
Sign up to set email alerts
|

Greenwashing Behaviours: Causes, Taxonomy and Consequences Based on a Systematic Literature Review

Abstract: This study used the systematic review methodology to examine peer-reviewed journal articles published in the Web of Science, ScienceDirect, Springer and Emerald Insight during the 2000–2020 period to analyse greenwashing. In an open market, the behaviours of state-owned enterprises (SOEs), private firms and multinational corporations (MNCs) pose an implicit greenwashing threat. Our focal point is to analyse corporate greenwashing in MNCs in host emerging markets, particularly in Asia, for two reasons. First, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 104 publications
(163 reference statements)
3
46
0
3
Order By: Relevance
“…The contributions of this paper are reflected in the following aspects: First, in previous studies, environmental responsibility is seldom carried out from the perspective of greenwashing under the background of internationalization of Chinese listed companies, which is a useful supplement to existing research [30,63,64] Second, diving factors of greenwashing from host countries are usually considered, such as institutional distance, which is used for researching the internationalization issues of an emerging market [1]. Compared with the above research, the driving factors of legitimacy pressures of a home country, including environmental regulation, public pressure, and industry pressure, are included in the scope of our research, and the theoretical mechanism is constructed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions of this paper are reflected in the following aspects: First, in previous studies, environmental responsibility is seldom carried out from the perspective of greenwashing under the background of internationalization of Chinese listed companies, which is a useful supplement to existing research [30,63,64] Second, diving factors of greenwashing from host countries are usually considered, such as institutional distance, which is used for researching the internationalization issues of an emerging market [1]. Compared with the above research, the driving factors of legitimacy pressures of a home country, including environmental regulation, public pressure, and industry pressure, are included in the scope of our research, and the theoretical mechanism is constructed.…”
Section: Discussionmentioning
confidence: 99%
“…As a specific external institutional pressure, industry competition strengthens firms' motivation to seek strategic deviation, alleviate external uncertainty, and demand for legitimacy [28][29][30]. Industry competition means that enterprises need to adapt to higher self-regulation and industry norms.…”
Section: Industrial Competition Pressure and Greenwashing Behavior Of...mentioning
confidence: 99%
“…According to the legitimacy theory, enterprises choose to disclose corporate environmental information in order to obtain legitimacy, and environmental information disclosure is a function of social and political pressure faced by enterprises. For enterprises with poor environmental performance, their legitimacy is more threatened by society than those with good performance, so they need to disclose more environmental information to relieve pressure from stakeholders (Yang et al, 2020). When taking Australian enterprises as research objects, Clarkson et al (2014) found that polluting enterprises do face greater social pressure and disclose more symbolic environmental information.…”
Section: Hypothesis Of Corporate Environmental Performance and Greenw...mentioning
confidence: 99%
“…If the environmental, social, and governance information disclosed by enterprises is unreliable, the greenwashing behavior of enterprises may become an obstacle to incorporating environmental, social, and governance factors into investment decisions ( Yu et al, 2020 ). Over time, greenwashing damages investor confidence and provokes negative market feedback ( Yang et al, 2020 ). At the same time, it inhibits investors’ optimism, and the positive promotion effect of carbon information disclosure on enterprise value fades with it.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%